Distribution of Radio News Stories by Telephone: A Louisiana Case Study - John R. Brooks (Journal of Applied Communications, 1988)
The Louisiana Cooperative Extension Service (LCES) initiated a 6-month study of delivery of radio news stories by telephone. The purpose was to identify stations not presently receiving Extension material, and to identify the subjects radio news personnel seem to prefer. The study was also intended to determine if stories could be distributed more efficiently and economically this way, rather than by mailing tapes directly to stations. Radio station personnel were given a telephone number to call and would ask for stories noted in a weekly package of broadcast news stories.